Enabling Richard: The Rhetoric of Disability in Richard III - Williams, Katherine Schaap (Disability Studies Quarterly, 2009)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> This article examines Shakespeare’s Richard III as an important example of staging disability in early modern drama. Although Richard’s character is taken by theorists as emblematic of premodern notions of disability, this article reads Richard instead as a “dismodern” subject who employs rhetorical power and performative ability to compensate for a bodily form marked with negative associations. Richard foregrounds his deformed figure in ways that advance his political power, appealing to bodily deformity and the impotence he claims it entails to obscure his shrewd political maneuvers. Understanding the powerful ends to which Richard uses his disability allows us to think about disabled identity in the Renaissance as a complex negotiation of discourses of deformity and monstrosity as well as a relation to bodily contingency that reveals the instability of all bodies. Keywords: deformity, disability, dismodern, drama, Shakespeare, Richard III.